8h+7=2(3h+2)+4+2h

Simple and best practice solution for 8h+7=2(3h+2)+4+2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8h+7=2(3h+2)+4+2h equation:



8h+7=2(3h+2)+4+2h
We move all terms to the left:
8h+7-(2(3h+2)+4+2h)=0
We calculate terms in parentheses: -(2(3h+2)+4+2h), so:
2(3h+2)+4+2h
determiningTheFunctionDomain 2(3h+2)+2h+4
We add all the numbers together, and all the variables
2h+2(3h+2)+4
We multiply parentheses
2h+6h+4+4
We add all the numbers together, and all the variables
8h+8
Back to the equation:
-(8h+8)
We get rid of parentheses
8h-8h-8+7=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation

See similar equations:

| 6x+12=8x+14 | | 1/2(6x-8)=11 | | 4.5+.75d=12 | | -20=6y+4(y+5) | | 18-(x+3)-2x=4+(x-5)x= | | 11x-15=3x-13 | | -7x=-10x-31 | | -(7-4x)-2x-(3x-9=-8 | | 2c+14=c+6 | | 4+180x=1125 | | -16(3m+4)=32 | | -1/2=1/7w-4/3 | | 6w+7(w-7)=29 | | -8v+42=54 | | 9-2v=-2v+8 | | 27=12w-9w | | 7g-15=-6g+20 | | 10(x+4)8x-(x+2)=10(x+4)8x-(x+2) | | -6y-4/5=5/3y-4/3 | | 20.91=4g+3.99 | | 6x=2x=24= | | 5n+2=9+6n | | 5y-2+4y+5y-2+4y=122 | | 5x−7=3x= | | 11x+3=1/121 | | |y+3|=5 | | 7n+6=17 | | 2(w-3)-6=-4(-5w+1)-2w | | 6p-6=-p+8 | | -14+8x=5(2+4x) | | 8(n-2)=24 | | x+7+4x=62 |

Equations solver categories